PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI PADA MATERI PERMINTAAN DAN PENAWARAN DI SMA N 15 PALEMBANG - nuryana92a; Neta Dian Lestari; Riswan Aradea (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2026)
The development of digital technology in education demands innovation in learning media that can improve students' understanding and interest in learning. This study aims to develop animated video learning media on the material on demand and supply for grade X students of SMA Negeri 15 Palembang and determine the level of feasibility, practicality, and effectiveness. The study uses the Research and Development (R&D) method with the PPE (Planning, Production, Evaluation) model. The results show that the media obtained a validation of 93.66% (very feasible), practicality of 86.25% (very practical), and an N-Gain value of 0.67 in the moderate category with effective interpretation. The novelty of the study lies in the dynamic visualization of the relationship between prices, quantity of goods, demand and supply curves, and market mechanisms through the integration of Canva, Gemini, and CapCut. Thus, the developed animated video media is feasible, practical, and effective for use in economics learning.